LİSE ÖĞRENCİLERİNİN SINIF İÇİ İSTENMEYEN DAVRANIŞLARI. - ELİTOK KESİCİ, Ayşe; YENGİN SARPKAYA, Pınar (Electronic Turkish Studies)
Class management's being conducted in an effective way results in gaining the particular aims of the lessons by the students. Students behaviors' ruining the learning environment occurs as an important problem and teachers opinions' about their hindering teaching are frequently encountered. With this study, in the classes of secondary education teachers from different branches, it is tried to be determined that what kind of behaviours that hinder the learning environment are encountered by teachers. In the research qualitative research method is used. Datas obtained from the research are analyzed according to intra class observations, teachers' and students' opinions. In the research, in 3 classes from 3 state schools, selected by random sampling, 160 hours intraclass observation is made; interviews are made with 15 students having education in the same classes and also 13 teachers teaching in the same classes. Findings obtained from observations and interviews are analyzed through content analysis and descriptive analysis from the programme NVivo 7. According to the results of the research, negative behaviours such as talking without permission, sending messages by cellphones, reading book in the lesson, sending messages to friends by papers, sleeping in the lesson, coming late to the class are obtained from the results of observations and interviews.